Recent advances in electrochemical copper catalysis for modern organic synthesis - Kim, Yemin; Jang, Won Jun (Beilstein Journal of Organic Chemistry, 2025)
In recent decades, organic electrosynthesis has emerged as a practical, sustainable, and efficient approach that facilitates valuable transformations in synthetic chemistry. Combining electrochemistry with transition-metal catalysis is a promising and rapidly growing methodology for effectively forming challenging C–C and C–heteroatom bonds in complex molecules in a sustainable manner. In this review, we summarize the recent advances in the combination of electrochemistry and copper catalysis for various organic transformations.
Keywords: copper; electrochemistry; radical chemistry; single-electron transfer; sustainable catalysis